MEMBIDIK MAHASISWA SEBAGAI CALON WIRAUSAHAWAN - Harsono, Harsono; Budiyanto, Sapto Mei (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The research main target is to give direction and guiding the students to study Entrepreneurship for their future choice job as the entrepreneur candidates. Entrepreneurship education is very brilliant idea in the era of very tight competion for job hunting for university graduaters, and this writing will give useful, valuable and meaningful contribution for students for being honest, reliable and kind heart entrepreneur in the future. The research kind is quantitative, entrepreneurship’ spirit is measured by Likert model attitude scale. The research instrument is questionnaire. The research design is survey, population 750 respondents, 150 samples are choosen by random sampling. Questionaires that are fulfilling the requirement is only 130. Then, it was cultivated SPSS method, and obtaining data presenting table and central tendency data analyzed by doubled linier regression. The research result showed that the entrepreneurship lesson score has influenced the students’motivation for doing business, and students’ study motivation also has influenced to study result entrepreneurship, though the influenced of both variables only 17 %. The growing of the entrepreneurship’spirit can be done if there was motivation and formal education was on. The formal education pushed the students to have positive attitude for doing entrepreneurship.